Simulation Study of Mid-infrared Supercontinuum Generation at Normal Dispersion Regime in Chalcogenide Suspended-core Fiber Infiltrated with Water - Chu Van, Bien; Dang Ngoc, Mai; Cao Long, Van; Nguyen Tuan, Hoang; Le Van, Hieu (Communications in Physics, 2020)
We report simulation results of supercontinuum generation in the suspended-core optical fibers made of chalcogenide (As2S3) infiltrated with water at mid-infrared wavelength range. Applying water-hole instead of the air-hole in fibers allows improving the dispersion characteristics, hence, contributing to supercontinuum generations. As a result, the broadband supercontinuum generation ranging from 1177 nm to 2629 nm was achieved in a 10 cm fiber by utilizing very low input pulse energy of 0.01 nJ and pulse duration of 100 fs at 1920 nm wavelength.